Peningkatan Pengenalan Konsep Angka dan Bentuk Geometri Melalui Penggunaan Alat Peraga Tangram Modifikasi Pada Anak Usia 5–6 Tahun di TK Al Falah - Santiah, Ai; Elnawati, Elnawati; Poppyariyana, Alfian Ashshidiqi (Bageur: Jurnal Ekonomi, Sosial, dan Pendidikan, 2026)
The introduction of the concept of numbers and geometric shapes is an important part of early childhood cognitive development which is the basis for logical and mathematical thinking skills. Based on the results of initial observations at Al Falah A Kindergarten, it was found that the ability of children aged 5-6 years to recognize the concept of numbers and geometric shapes is still not developed optimally. This is characterized by the fact that there are still many children who have difficulty in naming number symbols, counting the number of objects, and recognizing and mentioning simple geometric shapes. Therefore, it is necessary to use teaching aids that are attractive and in accordance with the characteristics of early childhood, one of which is through the use of modified tangram props. This research aims to improve the ability to recognize the concept of numbers and geometric shapes through the use of modified tangram teaching aids in children aged 5–6 years at Al Falah A Kindergarten. The research subjects were children in the age group of 5–6 years old at Al Falah A Kindergarten. Data collection techniques were carried out through observation, documentation, and performance assessment, while data analysis was carried out descriptively, qualitatively, and quantitatively. The results of the study show that the use of modified tangram props can improve children's ability to recognize the concept of numbers and geometric shapes. In the pre-cycle stage, children's abilities are still in the undeveloped category. After the implementation of the action in the first cycle, there was an increase but did not reach the success indicator. Furthermore, in cycle II, the child's ability increased significantly and achieved the criteria of developing very well. Thus, it can be concluded that the use of modified tangram teaching aids is effective in improving the introduction of the concept of numbers and geometric shapes in children aged 5–6 years in Al Falah A Kindergarten.